THE ANOMALY OF PRETRIAL AUTHORITY IN INDONESIAN LAW ENFORCEMENT: An Analysis of Decision Number 24/PID/PRA/2018/PN.JKT.SEL - Zico Junius Fernando (Jurnal Yudisial, 2024)
Pretrial Decision Number 24/PID/PRA/2018/PN.JKT.SEL, issued on 9 April 2018, became crucial in the Bank Century corruption scandal. In its ruling, Single-Judge Effendi Mukhtar ordered the Corruption Eradication Commission to continue the investigation or, if necessary, transfer the case to the police and the prosecutor’s office for further handling. It also clarified the legal status of senior officials, including former Bank Indonesia Governor Boediono, Deputy Governor Muliaman D Hadad, and former Secretary of the Financial System Stability Committee Raden Pardede. The decision sparked controversy due to the unclear legal status of certain defendants. This study employs a normative legal research method with a literature review using legislative, conceptual, and case-based approaches. This analysis is descriptive-prescriptive, examining legal sources and previous rulings. The result shows that the pretrial decision has sparked controversy and attracted significant legal attention. It extends pretrial authority by designating suspects not directly involved in the case. The ruling is assumed to exceed jurisdictional limits set by Article 1 point 10, Article 82 of the Criminal Procedure Code, Supreme Court Regulation Number 4 of 2016, and Article 53 of Law Number 48 of 2009, which may lead to injustice and undermine legal certainty for the defendant. Therefore, addressing this issue requires revising pretrial procedures, training judges and law enforcement, developing consistent guidelines, and strengthening oversight to ensure fairness and transparency.